(untitled) (Homoeopathy for All, 2025)
The AYUSH system, which encompasses Ayurveda, Yoga, Unani, Siddha, and Homeopathy, represents a rich legacy of traditional healing that continues to shape healthcare in India and beyond. Among these, Homeopathy has gained significant global recognition for its holistic, patient centered approach to treatment. Strengthening research in AYUSH, particularly in Homeopathy, requires integrating traditional wisdom with modern scientific methodologies to establish efficacy, ensure safety, and foster wider acceptance.